The relationships between parents' and children's screen times on body mass index: a cross-sectional path analysis - Kaori Ishii; Ai Shibata; Mohammad Javad Koohsari; Koichiro Oka (BMC, 2022)
Abstract Background Understanding factors contributing to an individual reducing screen time is essential for promoting a healthy weight. Parents' behavior affects children by influencing their daily decision-making through modeling, rules or restrictions, social support, and co-participation. We examined how the direct and indirect effects of parents' and children's behaviors regarding screen time influenced body mass index (BMI) among Japanese elementary school children. Methods We included 283 Japanese children, one child per household, aged 6-12 years, who were randomly selected from resident registries of two cities. The questionnaires were completed by children and their mothers and fathers. Screen time and sociodemographic attributes, including sex, age, employment status, height, and weight, were assessed using a mail-based survey. Path analyses were conducted to determine associations among children's, fathers', and mothers' variables. It was hypothesized that after controlling for household income and children's sex and age, mothers' and fathers' screen time on weekdays and weekends would be related to children's weekdays and weekend screen time, respectively. In addition, we hypothesized that children's weekday and weekend screen time was related to children's BMI. Results Both fathers' and mothers' weekday screen times were associated with children's weekday and weekend screen times. BMI was affected by children's weekday screen time (0.117). The path coefficients for the indirect effects of mothers' and fathers' screen time on children's BMI through children's weekday screen time were 0.016 from the fathers' weekday screen time and 0.024 from the mothers' weekday screen time (GFI = .980, AGFI = .953, RMSEA = .030, AIC = 93.030). Conclusions Both fathers' and mothers' weekday screen times indirectly affected children's BMI through children's weekday screen time among Japanese elementary school children. The strongest indirect effects could be seen by examining the paths of a mother's weekday screen time through children's screen time to BMI. Mothers who spend much time with their children are role models, and their behavior could affect the child's behavior. The findings imply that intervention strategies to reduce screen time in children should also focus on modeling the mothers' behavior.